PENERAPAN METODE DEMONTRASI UNTUK MENINGKATKAN KEMAMPUAN PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) KELAS III SD NEGERI 013 RAMBAH KABUPATEN ROKAN HULU TAHUN PELAJARAN 2016/2017 - Sutarno Sutarno (STKIP Rokania Pasir Pangaraian, 2018)
This study aims to improve the social science skills of students, through working on the plan and cardinal points. This technique is a form of developing learning activities to determine the plan and cardinal points correctly. The research subjects were grade III students of SD Negeri 013 Rambah Rokan Hulu in the 2016/2017 academic year. The research approach used is qualitative, while the type of research is Classroom Action Research (PTK). This study used 2 cycles, each cycle consisting of 4 stages, namely planning, implementing, observing and reflecting. The data analysis technique uses an interactive model analysis technique which consists of 3 components, namely: (1) data reduction (2) data presentation (3) drawing conclusions. Class III students of SD Negeri 013 Rambah. This can be seen from the increase in the percentage of results in cycle 1 and cycle 2. The final result of the implementation of this class action is that out of 21 students only 1 has not reached the KKM. Meanwhile, 20 students have fulfilled the KKM and even their scores are above the KKM